Local Economic Development through Potato Development Areas in Karamatwangi Village, Cisurupan District, Garut Regency. - Mandhaputri, Hafidzha Alfaisa; Aribowo, Aribowo; Riasih, Teta (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2023)
The village of Karamatwangi is one of the villages in Garut Regency that utilizes its natural potential to improve the welfare of the community by implementing local economic development as a community empowerment strategy through the agricultural sector. This research aims to provide an overview of: (1) partnerships established in the Potato Development Area, (2) job opportunities created in the Potato Development Area, and (3) economic activity improvements to understand how the Potato Development Area can benefit the income of agricultural laborers in the village of Karamatwangi. This research uses a qualitative descriptive method. Data sources used purposive sampling techniques to determine seven informants consisting of the Karamatwangi Village Government, Forest Village Community Institutions, business actors, andfarm laborers. Data collection techniques used in-depth interviews, observation, and documentation studies. The results showed that: (1) Potato Development Area activities have involved the active participation of the Karamatwangi Village community, (2) there are employment opportunities opened by the Potato Development Area, (3) there are increased skills obtained by farm laborers from the Potato Development Area. In the implementation of the PotatoDevelopment Area, there are obstacles related to the lack of increased income for farm laborers.This is because there has been no increase in the quality or quantity of potatoes produced, and thesale of potatoes still depends on loan sharks where the expansion of cooperation carried out by the Potato Development Area has not been widely opened. The lack of expansion of cooperation has an impact on increasing the income of farm laborers who currently farm laborers inKaramatwangi Village still have difficulty meeting their daily needs causing some farm laborers to be in debt to money lenders, local illegal banks (emok banks). Keywords: Local Economic Development; Community Empowerment; Income Generation.